Characteristics of Smith-Purcell Radiation and Grating Transition Radiation from Gratings with Variable Proﬁle - Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Shevelev M. V. Mihail Viktorovich; Shkitov D. A. Dmitriy Andreevich; Popov K. E.; Vukolov A. V. Artem Vladimirovich (Transition Radiation, 2019)
Title screen